Analisis customer engagement terhadap mobile e-sport gamer’s loyalty - Arissaputra, Rivaldi; Helmi, Arief; Hasan, Meydia; Amelia, Senna Rahma (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The spread of technology and information has now entered all sectors which causes more and more competition. The growing competition caused by the internet can be an opportunity to earn income. One of them is the application in the field of mobile e-sports, because it is viewed from the perspective of business structure, business model, prize money, and competitions that are classified as top level. The purpose of this study was to analyze the effect of customer engagement on mobile e-sport gamer's loyalty in Indonesia. Collecting data using a questionnaire with the measurement using an interval scale. The data collection technique used was purposive sampling with a total of 345 respondents. The analytical method used in this study was carried out using the Structural Equation Modeling (SEM) – Partial Least Square (PLS) method with the help of SmartPLS 3.0 software. The results showed that the customer engagement variable had an effect on gamer's loyalty..